Josip Jurčič – začetnik novinarskega stila - Kalin Golob, Monika (Jezik in slovstvo, 2022)
Between 1871 and 1881, Josip Jurčič edited Slovenski narod (Slovenian Nation), which in 1873 became the first Slovenian daily after moving from Maribor to Ljubljana. Daily publishing caused time constraints for the creation of texts and thus influenced the formation of journalistic style. The article shows how Josip Jurčič was able to do editorial work and examines the nature of his contribution to the development of journalistic texts and style, based on an analysis of the author's notes in the newspaper, evaluations of his work and a linguistic analysis of his first diary.
Keywords: first Slovenian daily; history of journalism style; journalism style; Jurčič, Josip; novinarski stil; prvi slovenski tednik; razvoj poročevalstva; Slovenian Nation; Slovenski narod